Importance of national and local level approaches to planning and development management of Lima - Flórez, Raúl (1986)
The main purpose of this paper is to examine the impact of the process of metropolitan planning within the context of national, regional and local development, as well as proposing some speciflc actions to achieve a more effective and participatory management in solving metropolitan and districtal problems. More specially the author suggests that in dealing with the most important problems of the city, by adequately managing investment of infraestructure and employment there could be as, a byproduct, a significant increase in the productivlty of the local urban administration, without having to increase even more the unfair difference in distribu tion of national resources among residents of Metropolitan Lima and those of other cities. The author concludes that in this way, local expectations of improving the quality of life can be matched with the development objectives in the country's socio economic policies and plans.